(3HgLI GdRef aj JGQjN SGOGJ Gdjefs - (3MSjf Hf YHO GdQMef Hf eMeO, GdMSjfj GdYdhqj GdgGTej, HOQ GdOjf, CHh eMeO, GHf GdnCrgnOd,J (B855 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdeJhMjO HGdYXeI hGdcHQjGA s
(3ChdgG agQS HGSeGA GdeJQLejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B240 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B15s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B96 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJGQjNs